Commentaries on the paper by Fox and collaborators on the morphology of juvenile stages of Ampulex compressa (Fabricius, 1781) (Hymenoptera: Ampulicidae) - Buys, Sandor Christiano (Zootaxa, 2007)
Herein I suggest corrections to the paper by Fox et al. (2006) on the juvenile stages of Ampulex compressa (Fabricius, 1781) (Hymenoptera: Ampulicidae). I was included as co-author of that paper because it was based upon specimens that I studied. However, I did not participate in the final elaboration of the manuscript. Throughout, the figures are numbered incorrectly on the actual plates; thus, figure 2 is actually figure 1, and figure 3 is actually figure 2. In the following, I refer to the figure numbers as they are on the plates themselves. More importantly, there are errors in morphological interpretation as follows: